Volum Atrium Kiri Pra-Bedah Sebagai Prediktor Fibrilasi Atrium Pasca Bedah Pintas Arteri Koroner - Juzni Alkatiri; Muhammad Munawar; Bambang B Siswanto (Jurnal Kardiologi Indonesia, 2009)
Background. Atrial fibrillation is the most common arrhythmia complication following coronary artery bypass graft (CABG). The incidence is raging from 10% to 50%. Previous studies have shown that an increasing left atrial (LA) volume is one of the risk factor in the occurence of atrial fibrillation following CABG.Aim. To investigate whether LA volume before CABG is an independent predictor for the occurence of atrial fibrillation following CABG.Methods. This is an observational cross-sectional study on patients underwent CABG in National Cardiac Center Harapan Kita. A thorough echocardiography examination, including the LA volume, was done and other clinical parameters were collected. The occurence of atrial fibrillation was observed during hospitalization.Result. One hundred patients were included in this study and using logistic regression analysis, we found that age (OR 1, 532 (CI:1,264 - 1,857); p < 0,001) and LA volume (OR 1,113(CI:1,042-1,189) are significantly correlated with the occurence of atrial fibrillation post-CABG. One mililiter increase in LA volume will increase 11% of the risk of atrial fibrillation following CABG.Conclusions. Left atrial volume age were independent predictors of atrial fibrillation following CABG.